2016
DOI: 10.31055/1851.2372.v51.n4.16341
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento anual de cuatro especies arbóreas con yemas desnudas nativas de los bosques templados húmedos de Patagonia.

Abstract: Summary: Annual growth of four naked-bud tree species from the temperate rainforests of Patagonia. Plant species inhabiting regions with low seasonality in climate tend to exhibit some morpho-architectural features that occur less frequently in species from regions with seasonal climate. This study was aimed at evaluating the primary growth of nursery-grown trees of four woody species native to the temperate rainforests of Patagonia, also known as Valdivian rainforests, where the degree of seasonality is lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…This is not the case of the present study, although we observed plants in similar ontogenetic stages and under non-limiting water conditions; that means extension durations recorded for rainforest species were higher (up to 15 weeks) than those for transitional forest species. For rainforest species, our results are similar to those reported for other Patagonian rainforest species in a recent common-garden study (Sosa and Puntieri 2016). Consequently, preliminarily, these results are in accordance with our initial hypothesis.…”
Section: Groupsupporting
confidence: 92%
“…This is not the case of the present study, although we observed plants in similar ontogenetic stages and under non-limiting water conditions; that means extension durations recorded for rainforest species were higher (up to 15 weeks) than those for transitional forest species. For rainforest species, our results are similar to those reported for other Patagonian rainforest species in a recent common-garden study (Sosa and Puntieri 2016). Consequently, preliminarily, these results are in accordance with our initial hypothesis.…”
Section: Groupsupporting
confidence: 92%
“…An alternative version of the nonadaptive argument is that the temperate zone as a whole should be thought of as having a winter climate inhospitable to exposed naked bud survival, but due to heterogeneity, certain specific subclimates or microclimates may still accommodate species with naked buds. Examples of specific subclimates that might be more suitable to species with naked buds occur in the treatment of Viburnum species in Europe (Kollmann & Grubb, 2002) and in the descriptions of naked‐budded species that occur in the temperate rainforests of Patagonia (Magnin et al ., 2012; Sosa & Puntieri, 2016). In a study on an evergreen broadleaved forest locale in central Japan, Nitta & Ohsawa (1998) argued that bud type could be associated with stratification in a temperate forest environment as the crowns of canopy trees are more exposed to temperature fluctuations and disturbances than the branches of the species that inhabit the shrub layer or understory (Kikuzawa & Lechowicz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, temperate, woody species with naked buds that lack cataphylls are often represented as rare or remarkable occurrences. Some of the hypotheses that have been put forward to explain the counterintuitive existence of naked buds outside of the wet tropics, for example, seek to identify temperate species with naked buds as anomalies restricted to mild subclimates or sheltered understory environments (Nitta & Ohsawa, 1998; Kollmann & Grubb, 2002; Magnin et al ., 2012; Sosa & Puntieri, 2016). In other instances, it is stated outright, as in Foster’s seminal work (1928) on cataphylls: ‘In a relatively small number of species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily to arctic hibernators, which inhabit alpine forests characterized by a marked seasonal pulse in the trophic offer (e.g. seeds from seasonal deciduous trees in chipmunks or grasses in yellow-bellied marmots [75,77]), Dromiciops lives in evergreen forests where the seasonal increase in food availability is slow and gradual [78][79][80]. Indeed, with climate change, the net primary productivity of temperate rainforests (also known as broadleaved forests) is being reduced due to the concomitant drought effect [6].…”
Section: (A) Predicting Survival To Warming In Heterothermic Animalsmentioning
confidence: 99%